Selective alterations of the host cell architecture upon infection with parvovirus minute virus of mice - Nüesch, Jürg P. F.; Lachmann, Sylvie; Rommelaere, Jean (Virology, 2005)
During a productive infection, the prototype strain of parvovirus minute virus of mice (MVMp) induces dramatic morphological alterations to the fibroblast host cell A9, resulting in cell lysis and progeny virus release. In order to understand the mechanisms underlying these changes, we characterized the fate of various cytoskeletal filaments and investigated the nuclear/cytoplasmic compartmentalization of infected cells. While most pronounced effects could be seen on micro- and intermediate filaments, manifest in dramatic rearrangements and degradation of filamentous (F-)actin and vimentin structures, only little impact could be seen on microtubules or the nuclear envelope during the entire monitored time of infection. To further analyze the disruption of the cytoskeletal structures, we investigated the viral impact on selective regulatory pathways. Thereby, we found a correlation between microtubule stability and MVM-induced phosphorylation of α/β tubulin. In contrast, disassembly of actin filaments late in infection could be traced back to the disregulation of two F-actin associated proteins gelsolin and Wiscott-Aldrich Syndrome Protein (WASP). Thereby, an increase in the amount of gelsolin, an F-actin severing protein was observed during infection, accounting for the disruption of stress fibers upon infection. Concomitantly, the actin polymerization activity also diminished due to a loss of WASP, the activator protein of the actin polymerization machinery the Arp2/3 complex. No effects could be seen in amount and distribution of other F-actin regulatory factors such as cortactin, cofilin, and profilin. In summary, the selective attack of MVM towards distinct host cell cytoskeletal structures argues for a regulatory feature during infection, rather than a collapse of the host cell as a mere side effect of virus production.
Available online 17 November 2004
Gesehen am 19.02.2021